Revitalizing the Walagara Tradition: A Solution for Household Harmony to Reduce Divorce Rates - Romli, Ahmad Syaifuddin; Billah, Ana (International Journal of Multidisciplinary Research of Higher Education, 2025)
The high divorce rate in Probolinggo Regency reflects a crisis in family resilience, driven by poor communication, economic instability, and shifting values due to modernization. This article explores the local tradition of Walagara, a Tenggerese cultural wisdom rich in values such as loyalty, mutual cooperation, deliberation, and spirituality, as an alternative solution to reduce the rate of divorce. This study aims to explore how the Walagara tradition, as part of the cultural heritage of the Tengger tribe, can strengthen family values and mutual respect within households. Using a qualitative approach and case study method, this research examines the relevance of Walagara in fostering marital harmony and the challenges of its implementation in the modern era. Findings reveal that the revitalization of Walagara values can be integrated into premarital education, family dialogue practices, and digital-based educational campaigns. This strategy emphasizes the involvement of traditional leaders, religious figures, communities, and youth to reinvigorate the tradition as a form of social capital. The study concludes that Walagara should not only be preserved as cultural heritage but also applied as a practical tool to strengthen family institutions in contemporary social contexts.